Pengaruh Employee Engagement, Job Design, dan Organizational Culture terhadap Kinerja Karyawan Bank Syariah Indonesia KC Palembang Demang - Dila Khairunnisa; Ulil Amri; Muhammad Iqbal (Indonesian Journal of Behavioral Studies, 2021)
This study aims to determine whether there is a relationship between employee engagement, job design, and organizational culture on the performance of employees of Bank Syariah Indonesia KC Palembang Demang. This study uses quantitative methods. The population is 60 employeesby using non-probability sampling, meaning that all employees have the same opportunity to be selected as samples. Based on the results of the study, it was concluded that 1) Employee engagement positive and significant effect on employee performance, as evidenced by the results of the t-test of 3.383, which is greater than t-table of 2.003 with a significance of 0.001 and a regression coefficient of 0.459. This shows that the higher the employee engagement, the higher the resulting performance. 2) Job design positive and significant effect on employee performance, as evidenced by the results of the t-test 2.114 which is greater than t-table 2.004 with a significance of 0.038 and a regression coefficient of 0.379. This shows that the higher the employee's job design value, the higher the resulting performance. 3) Organizational culture positive and significant effect on employee performance, as evidenced by tcount 2.463 which is greater than ttable 2.003 with a significance of 0.016 and a regression coefficient of 0.563. This shows that the better the organizational culture in an organization, the better the resulting performance.